2014
DOI: 10.5812/iranjradiol.14258
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Color Doppler Ultrasonography and Angiography to Assess Traumatic Arterial Injuries of the Extremities

Abstract: Background:Traumatic events are one of the major causes of arterial injuries. Physical examination is not a good predictor of the extent of injuries and arteriography is considered as the gold standard for this purpose. In the recent years, noninvasive modalities are increasingly replacing diagnostic arteriography. Color Doppler ultrasonography (USG) is an excellent method to investigate arterial diseases.Objectives:The present study aimed to evaluate the diagnostic value of color Doppler USG compared to conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…A flow rate of 30 cm/s or higher PSV represented normal arterial flow while a rate of 25 cm/s or lower PSV was considered to be arterial insufficient hence causing ED, and together with a normal arterial response, EDV > 6 cm/s and RI < 0.6 were considered to be normal [ 8 ]. In consistency with our findings, Pezeshki Rad et al [ 25 ] demonstrated that both sensitivity and specificity of CDDU in diagnosing traumatic limb vascular injury was much higher, proving that CDDU is a promising tool in screening and diagnosis. Additionally, all patients in the EHS 1/2 group had a single-peak spectrum in systole with no or a rather low spectrum of blood flow in diastole, while patients in the EHS 3/4 group all had an increased blood flow spectrum in both systole and diastole after erection.…”
Section: Discussionsupporting
confidence: 93%
“…A flow rate of 30 cm/s or higher PSV represented normal arterial flow while a rate of 25 cm/s or lower PSV was considered to be arterial insufficient hence causing ED, and together with a normal arterial response, EDV > 6 cm/s and RI < 0.6 were considered to be normal [ 8 ]. In consistency with our findings, Pezeshki Rad et al [ 25 ] demonstrated that both sensitivity and specificity of CDDU in diagnosing traumatic limb vascular injury was much higher, proving that CDDU is a promising tool in screening and diagnosis. Additionally, all patients in the EHS 1/2 group had a single-peak spectrum in systole with no or a rather low spectrum of blood flow in diastole, while patients in the EHS 3/4 group all had an increased blood flow spectrum in both systole and diastole after erection.…”
Section: Discussionsupporting
confidence: 93%
“…4,5,7,8 In our case also, the limb survived because of collateral circulation through the profunda brachii artery.…”
Section: Ramprasath Dr Et Al Int J Res Orthop 2017 Nov;3(6):1231-1234mentioning
confidence: 75%
“…7 However, this has its own disadvantages like time delay in shifting the patient to radiology department, expensive, etc. The alternative is doppler USG which has sensitivity of 95% and specificity of 92%.…”
Section: Ramprasath Dr Et Al Int J Res Orthop 2017 Nov;3(6):1231-1234mentioning
confidence: 99%
“…20 per cent of individuals who have suffered such damages are hospitalized, of which 200,000 death or permanent disability are created. 11,12 Damage to the head (head trauma) is the main cause of traumatic death in patients less than 25 years old and includes about one third of trauma deaths are. 13 In this study, the variable of trauma mechanism is a qualitative variable in which the highest frequency belongs to automobile driver (35.5 per cent) and the lowest frequency to Falling (9.4 per cent).…”
Section: Discussionmentioning
confidence: 99%